The Knowledge, attitude, skills, and satisfaction of village health volunteers toward the use of guidelines for community mental health assistance in the southern border context - Puti, Sarinda; Churat, Prenapa; Khun-inkeeree, Hareesol; Nochi, Hananmuhibbatuddin; Jii, Wasana (Journal of Research in Nursing-Midwifery and Health Sciences, 2024)
Objectives: 1) to study the results of developing knowledge, attitudes, and skills of village health volunteers (VHVs) using the learning process toward the use of guidelines for community mental health assistance in the southern border context 2) to study the satisfaction of VHVs with the learning process based on community mental health support tailored to the context of the southern border region. Methods: a descriptive research study with a sample group of 35 VHVs, working in the mental health community sector in three southern border provinces. Research tools included: 1) learning materials on the HUGS guidelines 2) semi-structured interview questionnaires covering knowledge, attitude, and skills with an IOC = .89, and reliability = .87 3) a satisfaction assessment questionnaire on the learning process with an IOC = 1., and Results: VHVs who participated in the learning process have gained significant knowledge, positive attitudes, and essential skills in providing mental health support within communities. Knowledge: Spiritual care, patient interview techniques, and communication and self-management. Attitudes: Value in helping others, positive attitudes and acceptance, heartfelt patient care, continuous self-development, and safety in practice. Skills: Active listening, positive communication for behavioral change, and applying spiritual principles. Conclusion: The learning process, based on the HUGS (humanized, understanding, giving, safety) approach and tailored to the context of southern border regions, has developed the VHVs' knowledge, attitudes, and skills in supporting mental health within their communities.